2019
DOI: 10.1155/2019/2416935
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Toxicity of Water Pipe Smoke Exposure in Mice and the Effect of Treatment with Nootkatone Thereon

Abstract: There is a worldwide increase in the popularity of water pipe (shisha) tobacco smoking including in Europe and North America. However, little is known about the effects of water pipe smoke (WPS) exposure on male reproductivity. We have recently demonstrated that WPS exposure in mice induces testicular toxicity including inflammation and oxidative stress. Nootkatone, a sesquiterpenoid found in grapefruit, has antioxidant and anti-inflammatory effects. However, the possible protective effect of nootkatone on WPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Furthermore, we found a significant increase in the concentration of cytochrome C in kidney homogenates. It has been demonstrated that exposure of mice to WPS induces oxidative stress leading to an elevation in cytochrome C release in testicular and heart tissue homogenates suggesting mitochondrial damage (Nemmar et al, 2017c;Ali et al, 2019). In addition, it has been shown that the cytokine tumor-necrosis factor α triggers cytochrome C release of from the mitochondria to the cytoplasm, which is known to attach with the adaptor apoptotic protease activator factor-I and recruit caspase-9/3 that eventually result in cellular apoptosis (Yu et al, 2014;Savitskaya and Onishchenko, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found a significant increase in the concentration of cytochrome C in kidney homogenates. It has been demonstrated that exposure of mice to WPS induces oxidative stress leading to an elevation in cytochrome C release in testicular and heart tissue homogenates suggesting mitochondrial damage (Nemmar et al, 2017c;Ali et al, 2019). In addition, it has been shown that the cytokine tumor-necrosis factor α triggers cytochrome C release of from the mitochondria to the cytoplasm, which is known to attach with the adaptor apoptotic protease activator factor-I and recruit caspase-9/3 that eventually result in cellular apoptosis (Yu et al, 2014;Savitskaya and Onishchenko, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NKT significantly reduced the activities of inflammatory enzymes such as superoxide dismutase (SOD), glutathione S-transferase (GST), cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS) and levels of glutathione (GSH), in addition to decreasing the total antioxidant capacity (T-AOC), as well as concentrations of malondialdehyde (MDA) and nitric oxide (NO) through inhibition of the Toll-like receptor 4/NF-κB/domains-containing-protein-3-inflammasome (TLR4/NF-κB/NLRP3) pathway [23]. NTK (90 mg Kg) was also shown to reduce the anti-inflammatory effects of cigarette vapor [24], as well as inhibit lung inflammation parameters via NF-κB inhibition [19]. Nevertheless, the mechanisms underlying the effects of NTK as an anti-inflammatory compound remain to be fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…After three-time washing, cells were analyzed using a flow cytometer. Malondialdehyde (MDA) content, superoxidase dismutase (SOD) activity, glutathione (GSH) level, and glutathione disulfide (GSSG) level were determined using commercial assay kits (Biovision, USA) according to the manufacturer's protocols as previously reported [16][17][18].…”
Section: Evaluation Of Oxidative Stressmentioning
confidence: 99%